Protection of Animated Cartoon Character: Copyright or Trademark? - Bayu Satriawan, I Gusti Ngurah; Marwanto, Marwanto (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 3 (2021), 2021)
Animated cartoon character is a character created or depicted in an animated story with the aim of supporting the story in an animated film. Currently, many children's clothes, bags, shoes or accessories include animated pictures from cartoons with the aim of attracting buyers' attention to increase sales of these products. The purpose of this writing is to identify, analyse and elaborate legal protections for animated cartoon characters based on the provisions in the copyright law, as well as legal protection for animated cartoon characters used as brands. This was normative legal research using a statutory, conceptual and analytical approaches. Animated cartoon characters as one of the objects of copyright protection, namely images, receive automatic protection based on the Copyright Law and can also be registered as Trademarks, as long as the image has distinctive power and has no similarity in substantial or in its entirety. However, if any parties who intend to use the animated cartoon characters that already classified as a well-known trademark, that party can propose a License to the owner of the trademark as regulated under the provision of Article 42 paragraph (1) of Trademark Law